Problems of Studying the Axiology of a Literary Text (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article examines the problem of axiology in artistic creativity, which is one of the current issues, since in the modern world people are beginning to forget about spiritual values and think more and more about material ones. The article studied the literature, namely: “Philosophy of the theory of values” by M. S. Kagan, “Values in the problem of peace: philosophical foundations and social applications of Constructive axiology” by N. S. Rozov, “The prob-lem of value in philosophy” by A . G. Kharchevoy. This work also analyzes the term “axiology” and its degree of study, significance in the modern world.